Case report: Exploring under the tip of the iceberg: A case series of “self-limiting” multisystem inflammatory syndrome in children - Meneghel, Alessandra; Martini, Giorgia; Balzarin, Marta; Zabadneh, Nadia; Fastiggi, Michele; Tirelli, Francesca; Zulian, Francesco (Frontiers in Pediatrics, 2022)
Multisystem inflammatory syndrome in children (MIS-C) is a serious condition triggered by SARS-COV-2 infection, characterized by persistent fever, multiorgan dysfunction and increased inflammatory markers. It requires hospitalization and prompt treatment, with nearly 60% of cases needing intensive care and 2% of fatality rate. A wide spectrum of clinical characteristics and therapeutic approaches have been reported in MIS-C. We describe a series of four patients with MIS-C, according to the available case definitions, followed in our Centre, with a self-limiting course without the need for immunomodulatory treatment (“self-limiting MIS-C”). Few data about self-limiting MIS-C are available and no information on medium to long-term follow-up of this subset of patients has been reported so far. Although limited, our experience provides new insights into MIS-C syndrome, highlighting a probably underestimated aspect of this disease that can have important therapeutical implications.